Tracing Historical Footsteps: Digitalizing Javanese Tafsīr Manuscript as a Pedagogical Resource for Contextual Islamic Education - Ulfah Rahmawati; Aziizatul Khusniyah; Sholihah Sholihah; M Khusnu Zain; Ika Nur Fitriani (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2026)
Javanese-language Quranic exegesis manuscripts written in the Arabic-Pegon script represent an intellectual heritage of Islam in Indonesia; however, their use in Islamic Religious Education (IRE) remains limited due to challenges regarding readability, accessibility, and pedagogical integration. This study aims to analyze the characteristics of manuscripts LSM 011 and LSM 012 and to explore the transformation of their digitized versions into learning resources for the sub-topic